Association between sleep duration and hypertension risk in patients with obstructive sleep apnea - Wang, Yi; Chen, Xi Xi; Lu, Fang Ying; Yan, Ya Ru; Li, Shi Qi; Zhang, Liu; Lin, Ying Ni; Li, Qing Yun (NPJ primary care respiratory medicine, 2025)
Obstructive sleep apnea (OSA) is a well-established risk factor for hypertension, with sleep duration being a modifiable factor influencing this risk. However, sleep misperception among OSA patients makes it unclear how subjective and objective sleep duration are associated with the prevalence and incidence of hypertension in this population. This study aims to examine these associations using data from the Sleep Heart Health Study cohort. Participants with OSA (apnea-hypopnea index ≥ 15 events/hour) were categorized based on objective sleep duration from polysomnography (PSGTST) and subjective sleep duration (morning-reported sleep time, AMTST; habitual sleep time, HABTST). Hypertension prevalence was assessed at baseline, while hypertension incidence was evaluated during a five-year follow-up. Multivariable logistic regression and Poisson log-link models were employed to explore the association between sleep duration and hypertension risk, with restricted cubic splines used to assess nonlinear trends. Among 2574 participants with OSA, 1263 had hypertension at baseline. Over 5.25 years, 376 of 1001 patients without baseline hypertension developed hypertension. Shorter PSGTST was linearly associated with higher hypertension prevalence ( p = 0.009) and incidence ( p = 0.024). HABTST showed a U-shaped relationship with hypertension prevalence, while AMTST was not significantly associated with either outcome. In patients with OSA, objective sleep duration is linearly and inversely associated with both the prevalence and incidence of hypertension, showing stronger and more consistent associations than subjective sleep duration measures. These findings highlight the value of incorporating objective sleep assessment in evaluating hypertension risk in this population.